Effect of SnO2 Addition on YBCO Superconducting Properties through Thermal Treatment Method - Kamarudin, Aliah Nursyahirah; Yeow, Tan Kar; Kechik, Mohd Mustafa Awang; Kien, Chen Soo; Pah, Lim Kean; Shabdin, Muhammad Kashfi; Hapipi, Nurhidayah Mohd; Karim, Muhammad Khalis Abdul; Doyan, Aris; Hong, Yap Siew; Shaari, Abdul Halim (Journal of Material Science and Radiation, 2025)
In this study, YBa2Cu3O7-δ (YBCO) superconductors were synthesized using a thermal treatment method with the addition of 1.0 wt. % SnO₂. The synthesis of YBCO employed nitrate-based precursors and polyvinylpyrrolidone (PVP) as a capping agent to enhance homogeneity during the synthesis process. All samples were characterized using thermogravimetric analysis (TGA), X-ray diffraction (XRD), Scanning electron microscopy (SEM) and Four-point probe (4PP). TGA results of the pure YBCO sample confirmed the complete transformation of nitrate-based precursors into oxide forms prior to the formation of the YBCO phase. XRD pattern revealed that Y123 as a major phase and Y124 as a minor phase in all samples with orthorhombic crystal structure were preserved. However, the peak intensity of the Y123 was pronounced with the addition of the SnO2 sample, suggesting the enhancement phase formation due to the presence of SnO₂. The electrical resistivity measures revealed a sharp superconducting transition in all samples. However, the reduction in superconducting transition temperatures for the SnO2 addition were observed where the Tc-onset decreased from 91.70 K to 89.25 K for the YBCO and YBCO + 1.0 wt.% of SnO2, respectively. This also exhibited the broadening of transition width, ΔTc indicating the suppression of superconducting properties with SnO₂ inclusion. SEM analysis showed notable differences in microstructure. The pure YBCO sample exhibited a larger average grain size of 1.32 µm, while the YBCO + 1.0 wt. % SnO2 sample formed small and rounded grains with smoother edges, potentially impacting intergranular connectivity and charge transport. Therefore, the addition of 1.0 wt. % SnO2 to YBCO enhanced the formation of the Y123 phase but adversely affected the superconducting transition temperature and microstructural features. These findings highlight the dual role of SnO2 in promoting phase purity while modifying grain morphology and electrical performance, offering insight into the optimization of dopants in high-temperature superconductors